Nuclear Receptors as Multiple Regulators of NLRP3 Inflammasome Function - Alatshan, Ahmad; Benkő, Szilvia (Frontiers in Immunology, 2021)
Nuclear receptors are important bridges between lipid signaling molecules and transcription responses. Beside their roles in several developmental and physiological process, many of these receptors have been described to regulate and determine the fate of immune cells and the outcome of immune responses under physiological and pathological conditions. While NLRP3 inflammasome is assumed as key regulator for innate and adaptive immune responses, and it has been associated with various pathological events, the precise impacts of the nuclear receptors on the inflammasome functions are hardly investigated. A huge variety of factors and conditions have been identified as modulators of NLRP3 inflammasome activation, and at the same time, many of the nuclear receptors are known to regulate and interact with these factors, including cellular metabolism and various signaling pathways. Nuclear receptors are attracting different aspects of the scientific field, as these receptors are easy to manipulate by lipid soluble molecules. Importantly, nuclear receptors mediate regulatory mechanisms at multiple levels: not only at transcription, but also in the cytosol via non-genomic effects. Their importance is also reflected by the numerous approved drugs that have been developed in the past decade to specifically target nuclear receptors subtypes. Researches aiming to delineate details of mechanisms that regulate NLRP3 inflammasome activation draw a wide range of attention due to their unquestionable importance in infectious and sterile inflammatory conditions. In this review we provide an overview of current reports and knowledge about NLRP3 inflammasome regulation from the perspective of nuclear receptors, in order to bring new insight to a potential therapeutic aspect in targeting inflammasome and inflammasome-associated diseases.